2012
DOI: 10.2337/db11-1243
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Isoprostane Overproduction in Diabetic Patients Treated With Aspirin

Abstract: Aspirin modestly influences cardiovascular events in patients with type 2 diabetes mellitus (T2DM), but the reason is unclear. The aim of the study was to determine whether in T2DM patients aspirin enhances platelet isoprostanes, which are eicosanoids with proaggregating properties derived from arachidonic acid oxidation by platelet NOX2, the catalytic subunit of reduced NAD phosphate oxidase. A cross-sectional study was performed comparing T2DM patients, treated (n = 50) or not treated (n = 50) with 100 mg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…In another study, Davi et al demonstrated that in obese patients, 10% weight loss was associated with a significant reduction of F2-IsoP (30). Due to the role of NADPH oxidase as an enzymatic pathway generating F2-IsoP, we analyzed the interplay between the two variables in patients with obesity or diabetes (22,86). In both settings, we found a coincidental overexpression of NADPH oxidase and isoprostanes with a significant correlation between them, suggesting that in patients at a risk of atherosclerosis, the increase of isoprostanes is partly dependent on NADPH oxidase activation.…”
Section: Laboratory Methodologymentioning
confidence: 93%
See 1 more Smart Citation
“…In another study, Davi et al demonstrated that in obese patients, 10% weight loss was associated with a significant reduction of F2-IsoP (30). Due to the role of NADPH oxidase as an enzymatic pathway generating F2-IsoP, we analyzed the interplay between the two variables in patients with obesity or diabetes (22,86). In both settings, we found a coincidental overexpression of NADPH oxidase and isoprostanes with a significant correlation between them, suggesting that in patients at a risk of atherosclerosis, the increase of isoprostanes is partly dependent on NADPH oxidase activation.…”
Section: Laboratory Methodologymentioning
confidence: 93%
“…Such interplay is useful to explain the tendency to venous and artery thrombosis in clinical settings, such as heart failure, cirrhosis, anoxia-reoxygenation, atrial fibrillation, and diabetes, all of which are characterized by the up-regulation of NOX2 and the over-expression of isoprostane (10,11,(20)(21)(22).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…23,34,35 Overgeneration of platelet nitric oxide is another mechanism that accounts for the antiplatelet effect of statins. Because of the negative effect of oxidative stress on nitric oxide biosynthesis and activity, 36 the impaired activation of NOX2-derived oxidative stress is likely to affect nitric oxide generation. Statins act by (1) inhibiting tissue factor synthesis and increasing thrombomodulin formation via inhibition of geranylgeranylation of the Rho/Rho kinase pathway and, in turn, nuclear factor-κB (NF-kB) activity; (2) increasing Kruppel-like factor 2 (KLF2) expression and endothelial nitric oxide synthase (eNOS) activity; (3) inhibiting oxidized low-density lipoprotein (oxLDL)-mediated CD36 and Toll-like receptor 4/6 (TLR4/6) activation; and (4) enhancing fibrinolysis.…”
Section: Statins and Platelet Activationmentioning
confidence: 99%
“…23 The association of statins with aspirin could be investigated in clinical settings in which the clinical usefulness of statins has never been explored, such as acute ischemic stroke, or in settings at risk of atherosclerotic complication, such as diabetes mellitus, in which the clinical efficacy of aspirin is less than expected. 36 An association between statins and aspirin would be of particular interest because statins could counteract the upregulation of isoprostanes elicited by aspirin in patients with type 2 diabetes mellitus. 36 Treatment of acute venous thrombosis or prevention of venous thrombosis recurrence in patients at risk may be another attractive setting in which the antithrombotic property of statins may become useful clinically.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation